2019
DOI: 10.1007/s00702-019-02045-5
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low frequency magnetic field induces human neuronal differentiation through NMDA receptor activation

Abstract: Magnetic fields with different frequency and intensity parameters exhibit a wide range of effects on different biological models. Extremely low frequency magnetic field (ELF MF) exposure is known to augment or even initiate neuronal differentiation in several in vitro and in vivo models. This effect holds potential for clinical translation into treatment of neurodegenerative conditions such as autism, Parkinson's disease and dementia by promoting neurogenesis, non-invasively. However, the lack of information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…it is known that tryptophan residues of the NMDAR play key roles in channel gating 481,482 . Moreover, exposure to low-intensity magnetic fields activates the NMDAR 225,242,268 .…”
Section: /72mentioning
confidence: 99%
See 1 more Smart Citation
“…it is known that tryptophan residues of the NMDAR play key roles in channel gating 481,482 . Moreover, exposure to low-intensity magnetic fields activates the NMDAR 225,242,268 .…”
Section: /72mentioning
confidence: 99%
“…In that work, 100 µT induced more oxidative stress compared to 50 µT 224 . Furthermore, Özgün et al reported that exposure to a magnetic field (1 mT, 50 Hz) in vitro induced human neuronal differentiation through N-methyl-d-aspartate (NMDA) receptor activation 225 . They observed that magnetic field enhanced intracellular Ca 2+ levels.…”
Section: Low-frequencymentioning
confidence: 99%
“…ELF-EMFs have been shown to influence cell migration and proliferation, and regulate mitogen activated protein kinase (MAPK) and extracellular signal-regulated kinase (ERK), promoting the following angiogenic process. In vitro and in vivo experiments revealed that ELF-EMFs impact the modulation of VEGF-dependent signal transduction pathways and increase the number of angiogenesis factors [ 64 , 65 , 66 , 67 ]. Furthermore, Fan et al showed that ELF-EMFs may increase the proliferation of Human Bone Marrow Stromal Osteoprogenitor Cells (hBM-SCs), promoting DNA synthesis and increasing the proportion of cells in the S phase, and up-regulating the expressions of hematopoietic growth factors both in hBM-SCs and mesenchymal stem cells (MSC) [ 68 ].…”
Section: Emf-elf and Wound-repair: Mechanism Of Actionmentioning
confidence: 99%
“…system. It is reported that low-frequency magnetic fields: (i) can active N-methyl-D-aspartate receptors in glutamatergic Ca 2+ channels to promote neuronal differentiation (Ozgun et al, 2019); (ii) may improve depressant behavior and cognitive dysfunction mainly by modulating synaptic function (Yang et al, 2019). However, repeated stimulations of intracranial nerves may bring inestimable side effects, and the penetration depth is relatively limited.…”
Section: Acikan Et Al 2018 Distraction Osteogenesismentioning
confidence: 99%